Pro Python 3 : features and tools for professional development - Browning, J. Burton; Alchin, Marty (ITpro collection, 2019)
"Refine your programming techniques and approaches to become a more productive and creative Python programmer. This book explores the concepts and features that will improve not only your code but also your understanding of the Python community with insights and details about the Python philosophy. "Pro Python 3, Third edition" gives you the tools to write clean, innovative code. It starts with a review of some core Python principles, which are illustrated by various concepts and examples later in the book. The first half of the book explores aspects of functions, classes, protocols, and strings, describing techniques which may not be common knowledge, but which together form a solid foundation. Later chapters cover documentation, testing, and app distribution. Along the way, you'll develop a complex Python framework that incorporates ideas learned throughout the book. Updates in this edition include the role of iterators in Python 3, web scraping with Scrapy and BeautifulSoup, using Requests to call web pages without strings, new tools for distribution and installation, and much more. By the end of the book you'll be ready to deploy uncommon features that can take your skills to the next level in Python."--Provided by publisher